SUSTAINABLE IMPROVEMENTS IN OIL AND GAS PRODUCTION (2025)
This book explores the importance of hydrocarbons in various aspects of human existence, including their recovery. It highlights the need for renewable energy sources and discusses the hydrocarbon formation process, drilling procedures, and reservoir production obstacles. It also discusses condensate banking, a problem in retrograde condensate reservoirs, and the development of a wettability alteration agent from surface-modified nanoparticles to enhance hydrocarbon recovery. Additionally, the study investigates the feasibility of using partly hydrophobic nanoparticles to enhance foam stability in oil recovery. The authors suggest that adding nanoparticles with changed wettability can improve the performance of traditional surfactant-stabilised foam. The study also examines the interplay between nanoparticles and wettability alteration, focusing on changes in interfacial energy, modulation of contact angles, and surface functionalisation. Similarly, the book also discusses the application of nanoparticles in enhanced oil recovery (EOR) techniques, which involve the injection of various chemicals. Nanoparticles have shown significant benefits in EOR applications due to their small size, significant surface energy, and adaptability to incorporate multiple functionalities. However, applying nanoparticles in EOR has drawbacks, such as agglomeration and precipitation in porous media, leading to core plugging and reduced permeability and oil recovery. In conclusion, this book provides a comprehensive understanding of the sustainable improvements in oil and gas production. By addressing these challenges and developing effective recovery techniques, the oil and gas recovery can be significantly improved.